Strategic environmental policy and the mobility of firms - Philipp M. Richter; Marco Runkel; Robert C. Schmidt (Center for Economic Studies and ifo Institute (CESifo), 2019)
The loss of international competitiveness of domestic industries remains a key obstacle to the implementation of effective carbon prices in a world without harmonized climate policies. We analyze countries' non-cooperative choices of emissions taxes under imperfect competition and mobile polluting firms. In our general equilibrium setup with trade, wage effects prevent all firms from locating in the same country. While under local or no pollution countries achieve the first-best, under transboundary pollution taxes are inefficiently low and lower than under autarky where only the `standard' free-riding incentive distorts emissions taxes. This effect is more pronounced when polluting firms are mobile.
Keywords: F12; F18; H23; 330; strategic environmental policy; firm location; carbon leakage; general equilibrium